Recent Development of Bone-Conductive Microphone in DSP (International Journal of Scientific Research and Management (IJSRM), 2014)
This article presents recent developments on ongoing challenges in bone conduction hearing devices. In view of the large number of problems and challenges in electronics for medical devices, this article focuses on areas that will advance bone conductive microphone devices for hearing aids. It will be described in greater details in the upcoming that the bone conduction microphone need to receive increasing attention and have found uses in many aspects of voice signal processing . This device can improve the quality of life for patients suffering from different hearing aids and make it feasible to use this technology all over the world.